הקוסמוס המאגי של יוחנן אלימנו: מאגיה נוצרית ויהודית בשירותו של מקובל - סופר, גל (מחשבת ישראל, 2020)
Yohanan ben Isaac Alemanno (1435-1505?) was an Italian kabbalist, philosopher and physician. In his less known autograph, Paris, BnF héb. 849, he incorporated contemporary Christian magic sources with kabbalah, providing a practical method to ascend to the upper worlds for gaining prophecy. This article brings together Alemanno’s autograph and contemporary magical works, in order to demonstrate a radical change in Alemanno’s approach towards demonic magic, and the way he interpreted it using a cosmology he developed. Then, Alemanno’s cosmology will be used for reconsidering a concept of Giovanni Pico della Mirandola (1463-1494): The Triplex Merkabah.